Using Actor-Based Theories Of Change to Conduct Robust Contribution An alysis in Complex Settings - Koleros, Andrew; Mayne, John (Canadian Journal of Program Evaluation, 2019)
The use of theories of change (ToCs) is a hallmark of sound evaluation practice. As interventions have become more complex, the development of ToCs that adequately unpack this complexity has become more challen ging. Equally important is the development of evaluable ToCs, necessar y for conducting robust theory-based evaluation approaches such as con tribution analysis (CA). This article explores one approach to tacklin g these challenges through the use of nested actor-based ToCs using th e case of an impact evaluation of a complex police-reform program in t he Democratic Republic of Congo, describing how evaluable nested actor -based ToCs were built to structure the evaluation.
Keywords: Behavioural strategy; COM-B